A Synthetic Cell-Penetrating Peptide Antagonizing TrkA Function Suppresses Neuropathic Pain in Mice - Wei-Ying Ma; Eri Murata; Koyo Ueda; Yoshihiro Kuroda; Ming-Hui Cao; Mineo Abe; Kenji Shigemi; Munetaka Hirose (Elsevier, 2010)
Nerve growth factor (NGF) and its high-affinity receptor, TrkA, are one of the targets in the production of new drugs for the treatment of neuropathic pain. NGF contributes to both the initiation and maintenance of sensory abnormalities after peripheral nerve injury. This study examined the effects of IPTRK3, a new synthetic cell-penetrating peptide that antagonizes TrkA function, on neuropathic pain in mice. Partial sciatic nerve ligation (PSNL) was used to generate neuropathic pain, and we injected IPTRK3 (2 or 10 mg/kg) intraperitoneally on day 7 after PSNL. Effects of the peptide on hyperalgesia, allodynia, and expression of Fos in the spinal cord were examined. Single administration of the peptide on day 7 significantly suppressed both thermal hyperalgesia and mechanical allodynia. Gentle touch stimuli-evoked Fos expression in the lumbar spinal cord was also significantly reduced. Intraperitoneal injection of a cell-penetrating peptide antagonizing TrkA function appears effective for treatment of neuropathic pain in a mouse pain model. Keywords:: cell-penetrating peptide, neuropathic pain, Tat, TrkA